Umweltethik und der mensch, Die: über intrinsische werte in der natur - Rolston, Holmes, 1932-2025, author; Max-Himmelheber-Stiftung, publisher (Colorado State University. Libraries, 2004)
Although much of the urgency for conserving biodiversity arises from our duties to other humans, with nature instrumental to what humans have at stake in their environments, a deeper environmental ethics recognizes intrinsic values in and duties directly to nature. Such duties arise because values are present at the levels of animals, living organisms, endangered species, and ecosystems as biotic communities. Ultimately and increasingly, we are responsible for and to Earth as planet and biosphere. Only people can be ethical, but this does not mean that only people count in ethics; to the contrary we are fully human only when we appropriately respect life on Earth in all its rich biodiversity.
Environmental ethics and humans: on intrinsic value in nature
A similar article is online in English at: http://hdl.handle.net/10217/48077.
Keywords: value in nature; intrinsic value; instrumental value; animals; organisms; endangered species; ecosystems; biosphere; Earth